2018
DOI: 10.2196/preprints.12939
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation of Limb Bioimpedance to Echocardiographic Indicators of Congestion in Patients with NYHA Class II/III Heart Failure (Preprint)

Abstract: BACKGROUND The treatment of heart failure (HF) in the United States is estimated to exceed $30 billion each year and is anticipated to increase to a staggering $70 billion by the year 2030. This makes the management of HF one of the leading challenges Medicare will face in the years to come. Traditional methods to detect impending congestion such as body weight and physical examination findings are often non-specific and lack sensitivity making them inadequate to recognize fluid overl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…9,10 Previous studies showed that data obtained by BIA were useful for treating HF. [11][12][13] In addition, several studies have suggested that oedema status, based on the ratio of ECW to TBW called oedema index (EI), is a factor indicating HF severity and prognosis of patients with HF. 14,15 There is a lack of clinical data indicating the usefulness of EI for acute decompensated HF with high sBP on admission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Previous studies showed that data obtained by BIA were useful for treating HF. [11][12][13] In addition, several studies have suggested that oedema status, based on the ratio of ECW to TBW called oedema index (EI), is a factor indicating HF severity and prognosis of patients with HF. 14,15 There is a lack of clinical data indicating the usefulness of EI for acute decompensated HF with high sBP on admission.…”
Section: Introductionmentioning
confidence: 99%
“…However, electrical currents at high frequencies are able to pass through the cell membrane, meaning that both ICW and ECW, which comprise total body water (TBW), are measured 9,10 . Previous studies showed that data obtained by BIA were useful for treating HF 11–13 . In addition, several studies have suggested that oedema status, based on the ratio of ECW to TBW called oedema index (EI), is a factor indicating HF severity and prognosis of patients with HF 14,15 …”
Section: Introductionmentioning
confidence: 99%